Beyond the Bible : moving from scripture to theology - Marshall, I. Howard; Vanhoozer, Kevin J.; Porter, Stanley E., 1956- (Grand Rapids, Michigan : Baker Academic, 2004)
Applying scriptural insight to contemporary issues is one of the most important, yet most difficult, tasks that the church faces. The Bible, though written long ago, can speak authoritatively to contemporary ethical, doctrinal, and practical issues. Respected author I. Howard Marshall offers guidance for this perennial task in Beyond the Bible. Using a ""principled approach, "" Marshall moves from Scripture itself to contemporary understanding and application of Scripture. He examines how principles can be established from Scripture, whether explicitly or implicitly
Hermeneutics, biblical interpretation and theology: Hunch, Holy Spirit or hard work/ Stanley E. Porter
Includes bibliographical references and index
Keywords: Bible. N.T. -- Hermeneutics; Bible. N.T. -- Theology; Dogma, Development of; Theology, Doctrinal